2019
DOI: 10.1371/journal.pone.0218208
|View full text |Cite
|
Sign up to set email alerts
|

A design of experiments approach for the rapid formulation of a chemically defined medium for metabolic profiling of industrially important microbes

Abstract: Geobacillus thermoglucosidans DSM2542 is an industrially important microbe, however the complex nutritional requirements of Geobacilli confound metabolic engineering efforts. Previous studies have utilised semi-defined media recipes that contain complex, undefined, biologically derived nutrients which have unknown ingredients that cannot be quantified during metabolic profiling. This study used design of experiments to investigate how individual nutrients and interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…There are three nodes in single hidden layer of ANN. Sigmoid activation functions were used, cross-validation of 19 of the media formulations defined in the second DOE iteration were randomly selected and withheld from ANN training set to do validation studies [59].…”
Section: Stepwise Regression and Artificial Neural Network Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three nodes in single hidden layer of ANN. Sigmoid activation functions were used, cross-validation of 19 of the media formulations defined in the second DOE iteration were randomly selected and withheld from ANN training set to do validation studies [59].…”
Section: Stepwise Regression and Artificial Neural Network Modellingmentioning
confidence: 99%
“…Historically several attempts have been made to design defined or semi-defined media recipes that do not require bio nutrient additives. Traditionally, media developed generally utilise one-factor-at-atime (OFAT) where all but one ingredient (factor) is fixed [58,59]. This approach guides towards determining individual factors that influence culture growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cultivation of the pre-cultures, mLB (modified Luria-Bertani) medium was used as previously described [24]. The experiment was performed in a modified ammonium sulphate medium (ASM) [63], comprising 8.7 mM citric acid, 20.2 mM MgSO 4 , 10 mM K 2 SO 4 , 22.6 mM NaH 2 PO 4 , 0.8 mM CaCl 2 , 25 mM (NH 4 ) 2 SO 4 , 4.16 mM glucose and 1 mL each of the filter-sterilized trace elements: 6 mM H 2 SO 4 , 0.1 mM CuSO 4 , 0.2 mM CoSO 4 , 0.5 mM ZnSO 4 , 2.29 mM FeSO 4 , 0.3 mM NiSO 4 , 0.9 mM MnSO 4 and 0.1 mM H 3 BO 3 . The pH was adjusted to 6.8 with 4 M NaOH.…”
Section: Microorganism and Mediamentioning
confidence: 99%
“…DoE methods are very amenable to automation, as works by ( Carbonell et al, 2018 ) and ( Rajakumar et al, 2019 ) have demonstrated. They have been adapted to identify the media and culture conditions that maximize yield of the metabolic pathway ( Singleton et al, 2019 ) ( Azubuike et al, 2020 ), or the optimization of a cell-free system ( Spice et al, 2020 ). In the context of metabolic pathways, these methodologies have been applied to choose regulatory elements such as promoters ( Blazeck et al, 2012 ) and 5′UTR ( Salis et al, 2009 ), or to modify other popular dosage parameters such as plasmid copy number ( Ajikumar et al, 2010 ) and codon usage, ( Hanson and Coller, 2018 ; Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%